GENDER RELATED DIFFERENCES IN OUTCOMES FOLLOWING PERCUTANEOUS CORONARY INTERVENTIONS IN DIFFERENT AGE GROUPS OF PATIENTS WITH ST – ELEVATION ACUTE MYOCARDIAL INFARCTION - Gujejaini L.; Sharashidze N.; Pagava Z.; Mamatsahvili M.; Aladashvili L.; Taboridze I.; Saatashvili G. (European Scientific Journal, ESJ, 2015)
Background: Conflicting evidence exists in respect of gender differences in outcomes after Acute Coronary Syndromes (ACS). Aim: Evaluation of gender differences in outcomes after ST – elevation Acute Myocardial Infarction (STEMI) in different age groups of patients following percutaneous coronary interventions (PCI). Methods: We studied consecutive 292 female and consecutive 311 male STEMI patients who underwent PCI with stent implantation. Study individuals were divided into groups by the gender and age (<65, 65-75, >75 years). Patients with total ischemic time >4 hours were excluded from the study. In hospital, 45-day and one year outcomes (death from cardiovascular causes, repeated angiography and revascularization) were evaluated, as well as several factors which may influence disease outcomes. Results: Total death rate in hospital, during 45-days and one year period: in women - 0.168, 0.250, 0.438, in men - 0.161, 0.289, 0.408, differences were not significant (p> 0.05). In hospital death rate in study groups (age groups <65, 65-75,>75years): in women -0.112, 0.155, 0.257, in men -0.121, 0.176, 0.216. Forty five-day mortality rate in study groups: in women -0.135, 0.279, 0.338, in men- 0.226, 0.279, 0.471; one year mortality rate in study groups: in women -0.315, 0.419, 0.622, in men - 0.347, 0.419, 0.529. Differences are statistically significant in age group under 65 years (P<0.05). Age under 65 years is associated with lower probability of in hospital and 45 days mortality (OR -0.53, 95% CI 0.9 – 0.25, OR- 0.36, 95% CI 0.18-0.72) in females, as well as with one year mortality in females OR- 0.47 , 95%CI 0.28 -0.80 and 45 days mortality in males OR-0.35, 95%CI 0.59-0.99. Study showed significantly (P<0.005) higher rate of repeated angiography (0.154 vs 0.077) and revascularization (0.127 vs 0.026) in females as compared with men after STEMI following primary PCI with stent implantation, Conclusions: a) Mortality rates (in hospital, 45 days and one year) after STEMI in patients with ischemic time <4 hours who underwent PCI with stent implantation did not differ between genders; b) Women younger 65 years with STEMI after timely revascularization have better prognosis as compared with their male counterparts and females of other groups; c) Risk of one year repeated angiography and revascularization in one year is higher in female patients with STEMI following primary PCI with stent implantation.